2021
DOI: 10.1080/13880209.2021.1874028
|View full text |Cite
|
Sign up to set email alerts
|

A review of anti-inflammatory, antioxidant, and immunomodulatory effects of Allium cepa and its main constituents

Abstract: Context Allium cepa L. (Liliaceae), known as onion, is consumed throughout the world. Onion and its derivatives including saponins, aglycones, quercetin, cepaenes, flavonoids, organosulfurs, and phenolic compounds, showed various pharmacological properties and therapeutic effects. Objective Anti-inflammatory, antioxidant, and immunomodulatory effects of A. cepa and its main constituents, along with the underlying molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 136 publications
(222 reference statements)
0
59
0
Order By: Relevance
“…Inflammation can also be defined as a reaction to defend the body in eliminating factors that can cause damage and the formation of homeostasis in the body. This causes increased blood flow due to the increased permeability of capillaries and white blood cells to the site of inflammation, resulting in inflammatory symptoms such as redness, swelling and pain [ 82 ]. Several previous studies reported that the Allium species has several bioactivities, one of which is anti-inflammatory [ 83 , 84 , 85 , 86 , 87 ].…”
Section: Allium Species Leave Bioactivity and Test Methodsmentioning
confidence: 99%
“…Inflammation can also be defined as a reaction to defend the body in eliminating factors that can cause damage and the formation of homeostasis in the body. This causes increased blood flow due to the increased permeability of capillaries and white blood cells to the site of inflammation, resulting in inflammatory symptoms such as redness, swelling and pain [ 82 ]. Several previous studies reported that the Allium species has several bioactivities, one of which is anti-inflammatory [ 83 , 84 , 85 , 86 , 87 ].…”
Section: Allium Species Leave Bioactivity and Test Methodsmentioning
confidence: 99%
“…In addition, ointment extract gel reveals hypertrophic presternal scar defense [ 74 ]. It is often used in topical methods for care and mitigation of postoperative hypertrophic scars [ 3 , 4 ] and keloid surgery [ 75 ]. A. cepa -allantoinpentaglycan gel also cures hypertrophic skin skins [ 76 ] and enhances the aesthetic appearance of postoperative scars [ 77 ] and burning cells [ 78 ].…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“…Studies demonstrate that onion extract is capable of removing hypertrophic wounds too [ 3 ]. Regular intake of onions lowers the risk of colorectal, lung, liver, brain, stomach, ovarian, prostate, and breast cancer [ 4 ]. The function of antiplatelets is significantly influenced by genotype, climate, and vegetable storage period.…”
Section: Introductionmentioning
confidence: 99%
“…Various pharmacological effects such as antidiabetic, antihyperglycemic, antiparasitic, antifungal, antimicrobial, antiplatelet, anti-inflammatory, antioxidant, and antispasmodic properties were reported for the extracts of A. cepa and its different constituents [28,31,42,[47][48][49][50][51][52]. e preventive effects of the extracts of A. cepa on the vascular and heart diseases [53], neurodegenerative and antidepressant disorders [8], and cataract formation as well as improving effects on kidney function were also reported [6,54].…”
Section: Traditional and Pharmacological Effectsmentioning
confidence: 99%